The Effect of Using the Internet as a Learning Resource on Student Learning Independence and Learning Outcomes - Citra Rahmadhani Suwandi; Udin Sidik Sidin; Mustari S. Lamada (PT. Global Research Collaboration, 2026)
This study aims to determine how the use of the internet (X) as a learning resource affects learning independence (Y1) and learning outcomes (Y2) of grade XI students at SMKN 10 Makassar using an ex post facto research method with correlation analysis and a quantitative approach by collecting data through questionnaires distributed to students. The results of the homogeneity test on the variable of internet use (X) showed that the Levene statistical value was 0.375 with the first degree of freedom of 1 and the second degree of freedom of 64, and a significance of 0.543. From these results, it can be concluded that there was no significant difference in variability between the groups tested. Then, the results of the homogeneity test on the learning independence variable (Y1) The results of the homogeneity test show that the Levene statistical value is 2.085 with the first degree of freedom of 1 and the second degree of freedom of 64, and a significance of 0.154. From these results, it can be concluded that there is no significant difference in variability between the groups tested, because the significance value (sig.) is greater than the predetermined significance level (0.05). The results of the simple linear regression test on the variable of internet use as a learning resource (X) on learning independence (Y1) Based on the significance value in the coefficients table, a significance value of 0.000 < 0.005 was obtained, so it can be said that the variable X has a significant effect on the variable of learning independence (Y1). Then, based on the results of the simple linear regression test on the variable of internet use as a learning resource (X) on learning outcomes (Y2), based on the significance value in the coefficients table, a significance value of 0.208 > 0.005 was obtained, so it can be said that variable X does not have a significant effect on the variable of learning outcomes (Y2). Based on the t-value of -1.273 < t-table of 1.998, it can be concluded that variable X does not affect the learning outcome variable (Y).